Relationship between procrastination and academic stress in dental students from a Peruvian university, 2019 - Anduaga Lescano de Scerpella , Silvana (2024)
Objectives: To determine the relationship between procrastination and academic stress in Dentistry students. Materials and Methods: Observational, descriptive, cross-sectional and correlational study in 61 students of the IV semester of the Faculty of Dentistry of the University of San Martín de Porres, Lima, Peru. The variables were evaluated using the SISCO Inventory of academic stress and the Academic Procrastination Scale – EPA. The relationship between the variables was determined using Spearman’s correlation. Results: 95.1% of the students indicated they had academic stress. Students who presented higher levels of academic self-regulation used strategies to cope with stress (p=0.028). It was determined that students who have a higher incidents of academic procrastination with also tend to report psychological reactions associated with stress (p=0.033). Likewise, it was identified that students who had strategies to cope with stress (p=0.004) were the least likely to postpone academic work. Conclusions: 95.1% of the students described having experienced episodes of anguish, worry, anxiety or nervousness during the academic semester. The students who presented higher levels of academic self-regulation were those who had skills to cope with stress. Likewise, it is determined that students who apply stress coping strategies are those who present the habit of academic procrastination less frequently.